2010
DOI: 10.1242/jeb.037127
|View full text |Cite
|
Sign up to set email alerts
|

Eating chemically defended prey: alkaloid metabolism in an invasive ladybird predator of other ladybirds (Coleoptera: Coccinellidae)

Abstract: SUMMARYBy comparison with studies of herbivore physiological adaptation to plant allelochemicals, work on predator physiological adaptation to potentially toxic prey has been very limited. Such studies are important in understanding how evolution could shape predator diets. An interesting question is the specificity of predator adaptation to prey allelochemicals, given that many predators consume diverse prey with different chemical defences. The ladybird Harmonia axyridis, an invasive species in America, Euro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 49 publications
0
29
0
Order By: Relevance
“…The extent of egg predation depends on the defensive alkaloids present in eggs of individual species (e.g., Agarwala and Dixon 1992;Sloggett and Davis 2010). A striking asymmetry occurs between H. axyridis and many ladybird species.…”
Section: Proposed Mechanismsmentioning
confidence: 99%
“…The extent of egg predation depends on the defensive alkaloids present in eggs of individual species (e.g., Agarwala and Dixon 1992;Sloggett and Davis 2010). A striking asymmetry occurs between H. axyridis and many ladybird species.…”
Section: Proposed Mechanismsmentioning
confidence: 99%
“…In general, DNA detection times are a few to many hours (McMillan et al, 2007;Greenstone et al, 2007), while detection using ELISA, can extend to days (Sopp and Sunderland, 1989;Symondson and Liddell, 1995). Results from GC-MS are highly variable, because target chemicals, especially defensive ones, can be broken down (Sloggett and Davis 2010;Sloggett et al 2011), sequestered or may remain in the predator as unmetabolised compounds. While Sloggett et al (2009) found that hippodamine from single H. convergens eggs persisted on average for 13.5 h in H. axyridis intraguild predators, Hautier et al (2008) found that adaline from a single A. bipunctata first instar larva could persist for many days.…”
Section: Detection Period Of Prey After a Predation Eventmentioning
confidence: 99%
“…Of the various stages, eggs are most likely to be attacked by predators, because they are immobile, poorly defended (Agarwala & Dixon, 1992;Felix & Soares, 2004;Michaud & Grant, 2004) and likely to be a high quality food (Gagné et al, 2002;Omkar et al, 2006). Many studies indicate that ladybird larvae fed conspecific (Gagné et al, 2002;Pervez et al, 2006;Roy et al, 2007) or heterospecific eggs (Pilipjuk et al, 1982;Pfannenstiel & Yeargan, 2002;Specty et al, 2003;De Clercq et al, 2005;Michaud & Jyoti, 2008) do better than when fed aphids whereas others indicate that conspecific and /or heterospecific eggs are inferior to aphids as food for ladybird larvae (Koide, 1962;Warren & Tadic, 1967;Takahashi, 1987;Rieder et al, 2008;Sloggett et al, 2009;Sloggett & Davis, 2010). Thus, the relative nutritive value of conspecific eggs, heterospecific eggs and aphids is a controversial issue.…”
Section: Introductionmentioning
confidence: 99%